C. B. GARCÍA ESTÉVEZ, J. MARÍA ROVIRA (eds.) - Enric Miralles. Archigraphias, 1983-2000 - Blanco, Arturo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Carolina B. García-Estévez, Josep María Rovira (eds.) Enric Miralles. Archigraphias, 1983-2000 Madrid: Abada editores, 2020. 448 pp. Softcover. Language: Spanish. 25 € ISBN: 978-84-17301-04-0